Genomic signatures of selection in Brangus cattle revealing the genetic foundations of adaptability and production traits using a breed of origin approach - Zayas, Gabriel A.; Mateescu, Raluca G. (Frontiers in Animal Science, 2025)
IntroductionThe composite breed Brangus combines the resilience and adaptability of the Bos t. indicus breed Brahman with the superior meat quality and fertility traits of the Bos t. taurus breed Angus. Its diverse genetics not only enables optimal production performance but also adaptability to hot and humid environmental conditions. From a research perspective, this makes Brangus an ideal model for identifying genomic signatures that reveal the effects of both artificial selection and natural adaptation. The aim of this study was to detect genomic signatures of selection by analyzing changes in breed origin of allele (BOA) frequencies across the genome.MethodsUsing a multi-breed Angus and Brahman herd (n = 4,516) as a reference, population structure was measured via principal component analysis and admixture analysis in two commercial Brangus herds (n = 4,720). BOA was estimated in these herds using LAMP-LD, followed by a signature of selection analysis utilizing a median-based Z-score approach and Fst analyses to detect genomic regions under selection.ResultsThe analysis revealed a genome-wide increase in Angus ancestry in both Brangus populations (71.46%, 68.7%), reflecting intense selection for traits associated with this lineage. BOA-based intra- and inter-population analyses identified significant shifts in Brahman and Angus ancestry across the genome, indicating potential selection for breed-specific genetics. Key genomic regions were identified on chromosomes 6, 8, 10, 12, 14, 17, 18, 19, 27, and 28, and were linked to traits such as fertility, growth, heat tolerance, carcass characteristics, and meat quality.DiscussionExpected genes showing signatures of selection included MC1R, responsible for black coat color, and PLAG1, integral to growth, fertility, and carcass traits, underscoring the effectiveness of this methodology. Novel genes under selection, such as CCNB2 (critical for fertility), MTCH2 (associated with meat quality and fertility) and PRLR (associated with coat length and heat tolerance), were also identified. These findings provide deeper insights into the genetic mechanisms driving adaptation and production performance in cattle and offer valuable information for strategic breeding practices aimed at optimizing the strengths of both parental breeds.